Hydrogen based energy storage - Arlt, Wolfgang; Müller, Karsten (Nova Science Publishers, Inc., 2013)
The transformation of the energy system towards a power generation based on renewable energies necessitates the implementation of storage technologies. A number of short term storage options exist and are already in use. However, large scale, long term storage can only be performed on hydrogen based chemical storage systems. Nevertheless, the low storage densities of hydrogen constitute a severe constraint of these concepts. To overcome this limitation hydrogen can be liquified, compressed or chemically transformed. A major focus of recent research activities has been the chemical transformation. A conversion into a carbon based fuel by Fischer-Tropsch or related processes is one possibility for this. The existing infrastructure and the high storage densities for this kind of fuels make this option very interesting even though the overall efficiencies are quite poor. A crucial requirement for the production of these fuels is the availability of a concentrated carbon oxide stream. A second option is the reversible storage of hydrogen on an organic carrier compound. Therefore an unsaturated compound is hydrogenated and later on dehydrogenated again, when the energy is needed. Certain constraints should be considered during the selection of the carrier material. For example, liquid compounds are easier to handle than solid or gaseous substances. Since the melting points of the hydrogenated and dehydrogenated forms often significantly vary, a close look on the phase change behavior is necessary. A big advantage of organic hydrogen carriers compared to other forms of chemical conversions of hydrogen is the fact that the hydrogen is released again as hydrogen. Therefore, the efficient power generation systems like fuel cells that are available for hydrogen can be used. The overall efficiency thus can be significantly increased compared to the conversion into fuels such as Fischer-Tropsch-gasoline. © 2013 Nova Science Publishers, Inc. All rights reserved.